PENGARUH PERMAINAN TRADISIONAL BOI-BOIAN DAN BENTENGAN TERHADAP KECEPATAN LARI 100 METER SISWA KELAS X SMKN 1 GERUNG - Bela Riska Putri Asir; Elya Wibawa Syariefoeddin; Sri Erny Muliyani (Journal Sport Science, Health and Tourism of Mandalika (Jontak) e-ISSN 2722-3116, 2024)
This study examined the effects of the traditional games boi-boian and bentengan on 100-meter sprint performance among tenth-grade male students of SMKN 1 Gerung. The study employed a quantitative quasi-experimental approach with a two-group pretest-posttest design. The population consisted of 18 students, all of whom were involved as research subjects and randomly assigned into the boi-boian group (n = 9) and the bentengan group (n = 9). The intervention was implemented for 18 sessions over six weeks. The instrument was a 100-meter sprint test, and the best time from three trials was recorded at pretest and posttest. Data were analyzed descriptively, followed by paired-sample t-tests and an independent-sample t-test on gain scores at a significance level of 0.05. The results showed that boi-boian significantly reduced sprint time from 13.81 ± 0.46 s to 12.87 ± 0.55 s (t = 12.24; p < 0.001), with an improvement of 6.82%. Bentengan also significantly reduced sprint time from 13.93 ± 0.61 s to 13.32 ± 0.60 s (t = 11.68; p < 0.001), with an improvement of 4.39%. The comparison of gain scores indicated that boi-boian produced a significantly greater improvement than bentengan (t = 3.56; p = 0.003). These findings indicate that both traditional games can be used to enhance sprint performance, although boi-boian provided the larger effect in this study.